2021
DOI: 10.1371/journal.pone.0260006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the early COVID-19 pandemic on outcomes in a rural Ugandan neonatal unit: A retrospective cohort study

Abstract: Background During the early COVID-19 pandemic travel in Uganda was tightly restricted which affected demand for and access to care for pregnant women and small and sick newborns. In this study we describe changes to neonatal outcomes in one rural central Ugandan newborn unit before and during the early phase of the COVID-19 pandemic. Methods We report outcomes from admissions captured in an electronic dataset of a well-established newborn unit before (September 2019 to March 2020) and during the early COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
(25 reference statements)
0
21
0
Order By: Relevance
“…The changing rates of low birth weight/preterm births described during COVID-19 were however, mixed overall, with seven (3%) reports noting decreased preterm/low birth weight [ 19 - 25 ], four (2%) reporting stable preterm/low birth weight [ 26 - 29 ], and two (1%) noting increased preterm/low birth weight [ 30 , 31 ]. Interestingly, the two reports noting increased preterm/low birth weight were both in low-income countries [ 30 , 31 ], while the other studies were all in high- or middle-income studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The changing rates of low birth weight/preterm births described during COVID-19 were however, mixed overall, with seven (3%) reports noting decreased preterm/low birth weight [ 19 - 25 ], four (2%) reporting stable preterm/low birth weight [ 26 - 29 ], and two (1%) noting increased preterm/low birth weight [ 30 , 31 ]. Interestingly, the two reports noting increased preterm/low birth weight were both in low-income countries [ 30 , 31 ], while the other studies were all in high- or middle-income studies.…”
Section: Resultsmentioning
confidence: 99%
“…While a reduction in childhood injuries might be expected due to lockdowns (which kept children from school and sports), the reduction in low birth weight/preterm births is somewhat surprising. These changing rates of low birth weight/preterm births were, however, inconsistent across studies, with seven (3%) reports noting decreased preterm/low birth weight [ 19 - 24 ,] five (2%) reporting stable preterm/low birth weight [ 25 - 29 ], and two (1%) noting increased preterm/low birth weight [ 30 , 31 ]. Interestingly, the two reports noting increased preterm/low birth weight were both conducted in low-income countries [ 30 , 31 ], while the other studies were all in high- or middle-income studies.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with the decline include health facility related barriers, perceived poor quality of care during the pandemic, pandemic-related anxiety, and others Nwafor et al [ 33 ] Prevalence and predictors of depression, anxiety, and stress symptoms among pregnant women during COVID-19-related lockdown in Abakaliki, Nigeria Malawi medical journal Cross-sectional study Nigeria COVID-19 related depression, anxiety, and stress symptoms among pregnant women Depressive symptoms, anxiety and stress were reported by pregnant women during the pandemic. Predictors of depression were multiparity and occupation whiles predictors of anxiety and stress included grand-multiparty, urban residence and trading Hedstrom et al [ 34 ] Impact of the early COVID-19 pandemic on outcomes in a rural Ugandan neonatal unit: A retrospective cohort study PLoS ONE Retrospective cohort Uganda Neonatal admissions and mortality There was decreased antenatal care. There was an increase newborn mortality during the early days of the COVID-10 pandemic Asratie et al [ 35 ] Unintended pregnancy during covid-19 pandemic among women attending antenatal care in northwest Ethiopia: Magnitude and associated factors International journal of women's health Cross-sectional study Ethiopia Unintended pregnancy Unintended pregnancy was found to be high during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…Delayed and decreased care can lead to more significant long-term disabilities and higher mortality rates in vulnerable populations. The decrease in hospital admission and increase in neonatal mortality rates were apparent during the pandemic [ 27 ], likely due to the disruptions of and decreased access to maternal and newborn care [ 34 ]. A 47 percent increase in facility neonatal deaths was reported in the first few months of the pandemic as a result of the disruption and diversion of health resources [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Kenya, the pandemic is said to have reduced inpatient utilisation and increased outpatient department (OPD) visits for sexual violence [ 8 ]. In Uganda, the pandemic is said to have indirectly increased pregnancy complications such as eclampsia and stillbirths and premature births due to delayed care-seeking behaviour [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%